Working time and rest time in the jurisprudence of the CJEU - Asquerino Lamparero, María José (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The right to limit the working day -and, consequently, the right to ensure mínimum times for rest- is considered a basic social principle. Base on this affirmation, the Court of Justice of the European Union has not ceased to dictate assertions that, in light of the judicial quiestions raised, try to settle whether the provisions of the Member States respect this fundamental right of the worker, always from the perspective of ensuring the safety and health. This fundamental objective provokes the inescapable need to contemplate the regulation that is called into question on the right to rest in expansive terms and, for this reason, the Court of Justice of the European Union does not settle for the formal designations that, where appropriate, the contractual parties may to offer. In this way, as it is intended to show in these lines, it is observed how the Court of Luxembourg when in doubt as to whether or not a certain period is part of the working day, relects to verify to what extent the worker remains committed to his employer. The provisions contained in Directive 2003/88/CE also shed light on other relevant issues that are directly related to the worker´s working day, also giving rise to other quiestions that, in relation to breaks and in particular vacations, the Court also contemplates in its pronouncements.
Keywords: working time; rest; holidays; guard; Directive 2003/88 EE